Effect of In Vitro Digestion on Free α‐Dicarbonyl Compounds in Balsamic Vinegars. Issue 4 (6th March 2013) - Papetti, Adele; Mascherpa, Dora; Marrubini, Giorgio; Gazzani, Gabriella
Abstract We investigated the influence of an in vitro simulated digestion process on the content of the free α‐dicarbonyl compounds most frequently found in food. A Glyoxal (GO), methylglyoxal (MGO), and diacetyl (DA) aqueous standard mixture and 2 brands of balsamic vinegar were analyzed before and after exposure to digestive enzymes. A strong matrix effect required adoption of validated RP‐HPLC‐DAD standard addition methods. The results showed that the digestive enzymes markedly alter the concentrations of the exogenous free α‐dicarbonyl compounds ingested with food; the extent of such changes varied with the α‐dicarbonyl compound itself and the diet components, which determined important but different food matrix effects also during digestion. The data also indicate that digestion can reduce the bioavailability of the toxic α‐dicarbonyl compounds ingested with food. However, no firm conclusions can be drawn about a putative positive influence of digestion on the toxic potential of dietary α‐dicarbonyl compounds, because their reaction in the presence of digestive enzymes likely gives rise to advanced glycation end products, which are involved in the development of chronic diseases.